Genetic And Morphological Variation Of The Sooty-capped Bush Tanager (Chlorospingus Pileatus), A Highland Endemic Species From Costa Rica And Western Panama - Chavarría Pizarro, Tania (2010)
We examined the effect of geographic isolation on morphology, genetic structure, and abundance of the Sooty-capped Bush Tanager (Chlorospingus pileatus), an endemic species restricted to highlands of Costa Rica and western Panama. Abundance and morphology were measured at five study sites and genetic variation was calculated from three microsatellite loci. We expected geographic discontinuities in this species’ distribution to have an effect on its morphology and genetic structure. Genetic variation was higher within than between populations with no effect of geographic barriers on population genetic divergence in this species, indicating gene flow is high between populations. Unique alleles were detected in each population and Fst values increased with geographic distance between populations. Some morphological traits differed between populations, which may be caused by adaptation to different selective pressures in each population. Molecular data did not differ between the two color morphs that coexist in two isolated populations, which were considered different species.